Game-based learning: Strengthening Islamic Religious Education learning process - Saskiah Saskiah (Dedicated: Journal of Community Services (Pengabdian kepada Masyarakat), 2023)
A pleasant situation in the learning process is one of the things that must be considered in the implementation of the learning process, including in Islamic Religious Education subjects. The implementation of Islamic Religious Education learning at SDN 2 Cantigi Kulon has been running smoothly but is still experiencing deficiencies in terms of student involvement. Therefore, efforts need to be made by teachers to increase student involvement. One effort that can be made is to use the game-based learning method, or game-based learning carried out through the smart snakes and ladders game, so that students are more enthusiastic and active in participating in the learning process. This article aims to describe the form of reinforcement carried out in Islamic Religious Education subjects wrapped in educational games using Islamic smart snakes and ladders games. This game involves cognitive and psychomotor skills that go hand in hand with concentration and questions about Islamic Religious Education learning materials. Students are asked to participate in the game of snakes and ladders and answer questions given by the teacher based on the flow of the game. Efforts to strengthen the subject of Islamic Religious Education with the game-based learning method using Islamic smart snakes and ladders are proven to be able to create a happy atmosphere for students, so that they are enthusiastic about participating in the learning process actively and responsively.   Abstrak Situasi yang menyenangkan pada proses pembelajaran merupakan salah satu hal yang harus diperhatikan dalam pelaksanaan proses pembelajaran, termasuk dalam mata pelajaran Pendidikan Agama Islam. Pelaksanaan pembelajaran Pendidikan Agama Islam di SDN 2 Cantigi Kulon telah berjalan dengan lancar namun masih mengalami kekurangan dari sisi keterlibatan peserta didik Maka dari itu, perlu dilakukan upaya yang dapat meningkatkan keterlibatan siswa oleh guru. Salah satu upaya yang dapat dilakukan adalah dengan menerapkan metode Game-based Learning atau pembelajaran berbasis permainan yang dilakukan lewat permainan ular tangga pintar sehingga para peserta didik lebih bersemangat dan aktif mengikuti proses pembelajaran. Artikel ini bertujuan untuk menggambarkan bentuk penguatan yang dilakukan pada mata pelajaran Pendidikan Agama Islam yang dibalut dengan permainan edukasi menggunakan permainan ular tangga pintar islami. Permainan ini melibatkan kognitif dan psikomotor peserta didik yang berjalan beriringan dengan konsentrasi dan pertanyaan-pertanyaan seputar materi pembelajaran Pendidikan Agama Islam. Peserta didik diminta untuk berpartisipasi dalam permainan ular tangga dan menjawab pertanyaan yang diberikan oleh guru berdasarkan alur permainan. Upaya penguatan pada mata pelajaran Pendidikan Agama Islam dengan metode Game-based Learning menggunakan ular tangga pintar islami ini terbukti dapat menciptakan suasana gembira bagi peserta didik, sehingga peserta didik antusias mengikuti proses pembelajaran secara aktif dan responsif. Kata Kunci: Antusiasme belajar; gamifikasi; pembelajaran berbasis permainan; permainan edukasi; ular tangga